Perception of men's need for preconception care—A qualitative exploration among health care providers and community members - Ojifinni, Oludoyinmola O.; Ibisomi, Latifat (Frontiers in Public Health, 2022)
Background: Several studies have shown that suboptimal health in men can result in poor reproductive health outcomes. The factors associated include lifestyle exposures and poor health-seeking behavior. The poor reproductive health outcomes can be mitigated through preconception care (PCC). PCC services for men are however rare. This qualitative study explored views about men's need for PCC in Nigeria. Methods: This exploratory qualitative study was done in Ibadan North Local Government Area, Oyo State, Nigeria. Focus group discussions were held with 12 religious leaders, 22 men and 23 women of reproductive age at the community level. There were key informant interviews with two community leaders and 26 health workers including specialist physicians and nurses at the primary, secondary, and tertiary health care levels. Transcribed data were analyzed thematically using inductive coding on MAXQDA. Results: The reasons participants proffered for men’s health requiring attention included men’s genetic contribution to pregnancy, treatment of low sperm count, and preventing transmission of infection to their partners. Participants stated however that men are often reluctant about accessing health services until complications arise. Opinions differed on men’s need for PCC: while some believed that men need PCC, others expressed contrary views stating that men do not require PCC as the service is more appropriate for women. Conclusion: Successful deployment and uptake of PCC services require the availability of the services and improved awareness about the need to optimize men’s health along with that of their partners.